2023
DOI: 10.1093/schbul/sbad002
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Insights of Schizophrenia via Single Cell RNA-Sequencing Analyses

Abstract: Background Schizophrenia is a complex and heterogeneous disorder involving multiple regions and types of cells in the brain. Despite rapid progress made by genome-wide association studies (GWAS) of schizophrenia, the mechanisms of the illness underlying the GWAS significant loci remain less clear. Study Design We investigated schizophrenia risk genes using summary-data-based Mendelian randomization based on single-cell sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Firstly, it solely focused on five kinds of molecular phenotypes, while there exist numerous other molecular features that warrant our attention, which may modulate the variants through distinct mechanisms. Moreover, the regulation of many genes is related to spatial context, so QTL effects of a particular cell type in a given developmental stage might be shadowed in this analyses based on bulk tissue [ 19 , 72 ]. Additionally, QTL data tend to be obtained from specific cohorts of individuals, it may influence the genes and gene functional enrichment results observed.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it solely focused on five kinds of molecular phenotypes, while there exist numerous other molecular features that warrant our attention, which may modulate the variants through distinct mechanisms. Moreover, the regulation of many genes is related to spatial context, so QTL effects of a particular cell type in a given developmental stage might be shadowed in this analyses based on bulk tissue [ 19 , 72 ]. Additionally, QTL data tend to be obtained from specific cohorts of individuals, it may influence the genes and gene functional enrichment results observed.…”
Section: Discussionmentioning
confidence: 99%
“…The exploration of the pathogenesis of COPD through genetic However, with the development of gene sequencing technology, it has been recognized that the regulation of numerous genes is specific to certain cells. Previous sequencing results based on a wide range of tissues may have resulted in the omission of information regarding expression quantitative trait loci (eQTLs) specific to certain cell subtypes [21]. Therefore, the utilization of scRNA-seq technology has become invaluable in the search for crucial COPD genes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the combination of MR analysis with scRNA-seq results may provide greater insight into the mechanisms of development of certain diseases. For example, Wu et al identified in their study that risk genes for schizophrenia were highly expressed in specific neuronal cells and clarified the causal relationship [ 21 ]. Indeed, expression quantitative trait loci (eQTLs) in lung tissues have gained some degree of discovery in the pathogenesis of COPD [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding gene expression changes is crucial because of their impact on neurotransmitter systems, synaptic formation, and neural circuitry, directly affecting behaviour and cognitive functions [59]. Techniques such as RNA sequencing can identify key genes and pathways that are dysregulated, offering insights into the genetic underpinnings of schizophrenia [60]. Simultaneously, examining synaptic plasticity, which encompasses the structural and functional changes in synapses responsible for learning and memory, is essential [17,25].…”
Section: Discussionmentioning
confidence: 99%